Mechanisms and indicators of socialization of the child with intellectual disorders - Татьянчикова, Ірина Володимирівна (Educational Dimension, 2017)
In the article the problem of the socialization of children with intellectual development has been considered. The emphasis on the features of modern education system has been made, its goals and objectives have been reconsidered. Systematic, gradual and consistent special pedagogical work, which aims to develop social activities that ensure effective capacity being a child with special needs in society is under the consideration. Theoretical and methodological foundations of the problem have been grounded; psychological content of the process of socialization has been found; authors involved in the problem of socialization, including fchildren with disabilities have been represented. It has been proved that increased attention to their socialization is a prerequisite for the social improvement of the society and the difficulties that arise primarily due to uncertainty of specific corrective actions. The purpose of the article is to determine the mechanisms of socialization and stages (adaptation, personalization, integration, employment stage), indicators of success for each of them. Different interpretations and diversity of views of scientists on the mechanisms that ensure the socialization process have been considere. The attention is drawn to the fact that there is no consensus on the mechanisms of socialization in the works of researchers, including those in the national psychology. The mphasis on the importance of the understanding of socialization review its performance has been made, the issue of the most significant indicators of its performance at each stage has been clarified. Valuable practical solution to the problem of socialization, positive software which significantly affects the comfort of life of people with intellectual disabilities in the new socio-economic conditions of society has been shown. The general terms of optimizing the socialization of students in the process of implementing corrective work in a special school for further research on the issue of socialization of people with disabilities have been defined.